2019
DOI: 10.1111/evj.13064
|View full text |Cite
|
Sign up to set email alerts
|

The lipidome of Thoroughbred racehorses before and after supramaximal exercise

Abstract: Summary Background A comprehensive study of the effect of supramaximal exercise in lipid homeostasis of Thoroughbreds provides the basis for future research on the role of lipids on energy metabolism in racehorses. Objective To compare the plasma lipidome of Thoroughbreds before and after supramaximal exercise using an untargeted lipidomics approach. Study design Pilot experimental study. Methods Four Thoroughbred horses were used. The maximal oxygen consumption (VO2 max) was calculated for each horse. Horses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Myriaste, a saturated long chain fatty acid, also showed an increase after exercise. Previous studies reported similar findings in endurance horses , and suggested that the changes may be attributed to either lipolysis of adipose tissue (i.e., unsaturated/saturated ratio is higher in adipose compared to resting plasma NEFA) or of the preferential utilization of specific fatty acids during exercise . Further examination of our data revealed a more pronounced decrease in medium chain saturated fatty acids after high-intensity exercise, whereas the moderate-intensity exercise group exhibited a more prominent increase in the long chain unsaturated fatty acid.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Myriaste, a saturated long chain fatty acid, also showed an increase after exercise. Previous studies reported similar findings in endurance horses , and suggested that the changes may be attributed to either lipolysis of adipose tissue (i.e., unsaturated/saturated ratio is higher in adipose compared to resting plasma NEFA) or of the preferential utilization of specific fatty acids during exercise . Further examination of our data revealed a more pronounced decrease in medium chain saturated fatty acids after high-intensity exercise, whereas the moderate-intensity exercise group exhibited a more prominent increase in the long chain unsaturated fatty acid.…”
Section: Discussionsupporting
confidence: 84%
“…To gain a more comprehensive understanding of the contribution of lipids to energy production in muscle, further studies are warranted and the development of techniques such as lipidomics is of primary importance. Recently, the lipidome of racehorses was characterized following treadmill exercise in a limited number of horses, showing promise in unravelling the involvement of lipids in horse racing …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lipidome's complexity and structural diversity, lipidomics can be considered as a unique subgroup of metabolomics research 39 . Studies on the equine lipidome are currently in their infancy but pilot work published in EVJ in 2019 has explored the impact of exercise on specific plasma lipids 40 …”
Section: Lipidomicsmentioning
confidence: 99%
“…Concerning acute bouts of exercise, there are comparatively few studies which analyzed exercise-induced lipidome changes [94][95][96]. In comparison to prolonged exercise and high-volume workloads, these studies documenting those alterations in lipidome levels were present in both exercises, but they manifested in much different ways.…”
Section: Lipidomic Profile In Acute and Chronic Physical Exercisementioning
confidence: 99%